A novel control strategy for quadrotors with variable mass and external disturbance. (2nd September 2021) - Zhao, Jing; Ding, Xiaoqian; Jiang, Bin; Jiang, Guoping; Xie, Fei
Abstract: Considering a class of quadrotor with variable mass of load and external disturbance, a novel control strategy based on adaptive non‐singular fast terminal sliding mode control is proposed to control in this article. Like external disturbances, internal disturbance caused by mass change will further affect the stability of the system and reduce the reliability of the system. Firstly, the dynamic modeling of a quadrotor with variable mass is carried out based on Euler Newton formulation. Then, a non‐singular fast terminal sliding mode controller based on adaptive integral backstepping is designed to overcome some external and internal disturbances. Meanwhile, an adaptive mass estimation algorithm is developed for real‐time mass estimation. Finally, through several groups of compared simulation results shows that the proposed method owns superior tracking performance for the quadrotor in both of mass change and external disturbance conditions.